Մտորումներ հայերէն տպագիր գրքի տեղային մատենագիտութիւնների մասին - Տէր-Վարդանեան, Գէորգ
The article discusses the bibliographies of the Armenian publications in Jerusalem, Iran, and Lebanon (eight books), pointing to the methods and means of preparing new, supplemented and amended editions of those bibliographies and, with their help, of improving the quality of general bibliographies of Armenian publications (books and periodicals). The main conclusion is that the National Library of Armenia, along with its fundamental task of compiling general bibliographies of Armenian books and periodicals, should coordinate and direct the preparation and publication of local bibliographies. Among many tasks, priority should be given to creating a complete annotated bibliography of all the publications of the Mekhitarist Congregation (of Venice and Vienna). В статье представлены библиографии армянских изданий Иерусалима, Ирана и Ливана (восемь книг), предложены способы и средства для составления новых, дополненных и улучшенных версий этих библиографий, а с их помощью, повышения качества обобщающих библиографий армянских печатных материалов (книг и периодики). Основным выводом является то, что Национальная библиотека Армении, наряду с ее фундаментальной задачей формирования общих библиографий армянской книги и прессы, должна координировать и направлять составление и публикацию местных библиографий. В ряду множества задач, первоочередной является создание полной аннотированной библиографии всех публикаций Конгрегации Мхитаристов (Венеции и Вены).
Keywords: Բանասիրութիւն